BENEFITS AND CHALLENGES OF TEACHER PROFESSIONAL DEVELOPMENT PROGRAM IMPLEMENTATION: ENGLISH TEACHERS’ PERSPECTIVES - Monica, Santa; Kuswandono, Paulus (International Journal of Indonesian Education and Teaching (IJIET), 2019)
This paper aims to discover benefits and challenges faced by English teachers along their involvement in Teacher Professional Development (TPD) programs in Yogyakarta. There were 73 senior high school English teachers in Yogyakarta city and Sleman regency as the participants in this research. The data were obtained through both quantitative and qualitative methods, distributed questionnaires and followed by in-depth interviews to five participants. The results of this paper firstly showed that some TPD programs were found to be beneficial perceived by the English teachers. Secondly, there were two major challenges faced by the participants, namely teachers’ workload & time management and also the lack of effective follow up programs. DOI: doi.org/10.24071/ijiet.2019.030212